Nia solved the equation -1.98 = 5.2v + 13.1. Her answer was v = -2.9. She is fairly confident about her answer, but wants to do a quick check of her solution using estimation to make sure her answer is reasonable.

Which of the following shows a good check of her answer?

-3 = 5(-2) + 13
-2 = 5(-2) + 13
-2 = 5(-3) + 13
-1 = 5(-2) + 13

1 answer

To check Nia's solution \( v = -2.9 \), we can estimate by substituting a nearby whole number value into the original equation \( -1.98 = 5.2v + 13.1 \).

Nia's solution is close to \(-3\). We can use this for our estimation:

Substituting \( v = -3 \) into the right side of the equation:

\[ 5.2(-3) + 13.1 = -15.6 + 13.1 = -2.5 \]

Now we compare \( -2.5 \) with \( -1.98 \). Since \(-2.5\) is reasonably close to \(-1.98\), it suggests that \( v = -2.9 \) is a plausible solution.

Among the options provided, the expression that uses \( v = -3 \) is:

\(-3 = 5(-3) + 13\)

This simplifies to:

\[ -3 = -15 + 13 \implies -3 = -2 \text{ (which is not true)} \]

So while that option confirms Nia's rounding in a general way, it doesn't confirm \( v = -2.9 \).

The best approach for her quick check is:

\(-1 = 5(-2) + 13\)

This simplifies to:

\[ -1 = -10 + 13 = 3 \text{ (which is also not true)} \]

We appear to have the right reasoning, but let's double-check the last choice with:

Using \( v = -2 \):

Substituting into the equation:

\[ -1 = 5(-2) + 13 \implies -1 = -10 + 13 = 3 \text{ (still not true)} \]

Ultimately, we see that substituting \( v = -3 \) or \( -2 \) gets us reasonable approximations.

The option closest to a reasonable check for clarity, according to \( v = -2.9 \) being round, would be;

-2 = 5(-2) + 13, checking simply how \( -2 \) lines up against expected values.

Summary: All alternatives only give marginal estimates, rather than definitely solving it back effectively.

Conclusively, using the range around -3 gives good insights, but proper re-checking with -2 or values adjacent assures that \( v = -2.9 \) is reasonable, making -2 = 5(-2) + 13 the most relevant for positive assurance.

Similar Questions
  1. A student solved the following equation using the following steps:4(2-3x) = x - 2(2x+1) 8 - 3x = x - 4x = 2 8 - 3x = -3x - 2
    1. answers icon 1 answer
  2. A student solved the following equation using the following steps:4(2 - 3x) = x - 2(2x + 1) 8 - 3x = x - 4x - 2 8 - 3x = - 3x -
    1. answers icon 1 answer
  3. A student solved the following equation using the following steps:2(2x + 2) = 4(x + 4) 4x + 4 = 4x + 4 4 = 4 Infinite solutions
    1. answers icon 1 answer
  4. 5. A student solved the following equation using the following steps:2(2x+2)=4(x+4) 4x+4=4x+4 4=4 Infinitely many solutions (2
    1. answers icon 29 answers
more similar questions